Music deculturation: A traditional thai Music tool for Indonesian Music Adoption - Surasak Jamnongsarn (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
There has been foreign music influence on traditional Thai music since Ayutthaya period. Pi Jawa ( Java flute), Klong Jawa ( Java drum) and some traditional Thai song with foreign title have been legally and literally evident in Ayutthaya era. Some said that Thai people are open-minded in music, harmonious mixing overseas music culture with their own. Ethnomusicologists have seen this social phenomenon via music context and explained the revolution of traditional Thai music differently from the acceptance of music in general. This article reviewed the acceptance of Indonesian music, including Javanese music from Central Java and Sundanese music from West Java, into the Javanese Idiomatic Melody in traditional Thai music and Angklung Thai style. Indonesian music was seriously and forcefully deculturated. Playing technique has been adjusted to suit Thai music playing. Tuning system of Javanese Gamelan in Thailand has been fine tuned to conform to that of Thai music. Physical appearance of Sundanese Angklung has been replaced with Angklung Thai style. Javanese song have undergone music elaboration and rewritten to satisfy Thai musicians, with approval from elite Thai musicians and previous Thai music institutes together with Thai people in the society.